Odpowiedź:
[tex]\frac{1}{81}*\frac{1}{9}*(\frac{1}{3})^{7}=\frac{1}{3^{4}}*\frac{1}{3^{2}}*(\frac{1}{3^{7} })=\frac{1}{3^{13}}=3^{-13}[/tex]
[tex](9*3^{9} *27):(3^{7}*3^{4})=(3^{2}*3^{9}*3^{3}):(3^{11})=3^{14}:3^{11}=3^{3}[/tex]
[tex](1000*(-10)^{8}):(10^{9})=(10^{3}*10^{8}):10^{9}=10^{11}:10^{9}=10^{2}[/tex]
[tex]81*(-3)^{5}*(-27)=3^{4}*(-3)^{5}*(-3)^{4}=3^{12}[/tex]
[tex](-\frac{1}{32})*\frac{1}{16}*(\frac{1}{2})^{6}=\frac{1}{-2^{5}}*\frac{1}{2^{4}}*\frac{1}{2^{6}}=\frac{1}{-2^{15}}[/tex]
Szczegółowe wyjaśnienie: